The platelet transcriptome and proteome in Alzheimer’s disease and aging: an exploratory cross-sectional study - de Sousa, Diana M. Bessa; Poupardin, Rodolphe; Villeda, Saul A.; Schroer, Adam B.; Fröhlich, Thomas; Frey, Vanessa; Staffen, Wolfgang; Mrowetz, Heike; Altendorfer, Barbara; Unger, Michael S.; Iglseder, Bernhard; Paulweber, Bernhard; et al. (Frontiers in Molecular Biosciences, 2023)
Introduction: Alzheimer’s disease (AD) and aging are associated with platelet hyperactivity. However, the mechanisms underlying abnormal platelet function in AD and aging are yet poorly understood. Methods: To explore the molecular profile of AD and aged platelets, we investigated platelet activation (i.e., CD62P expression), proteome and transcriptome in AD patients, non-demented elderly, and young individuals as controls. Results: AD, aged and young individuals showed similar levels of platelet activation based on CD62P expression. However, AD and aged individuals had a proteomic signature suggestive of increased platelet activation compared with young controls. Transcriptomic profiling suggested the dysregulation of proteolytic machinery involved in regulating platelet function, particularly the ubiquitin-proteasome system in AD and autophagy in aging. The functional implication of these transcriptomic alterations remains unclear and requires further investigation. Discussion: Our data strengthen the evidence of enhanced platelet activation in aging and provide a first glimpse of the platelet transcriptomic changes occurring in AD.